Not-so-itsy-bitsy spider - McGee, Joe; Skaffa, Teo (New York Aladdin, 2022)
"Adults are always telling kids that spiders are more afraid of them than they are of the spider. But what about when that spider is the size of a dog? And your parents are out? And you just saw it scuttle past the open doorway to the living room? You know it's waiting to jump out and eat you. You have no choice ... you have to find it before it finds you!"--
Ages 7-10.
112421
Keywords: Twins -- Juvenile fiction; Babysitters -- Juvenile fiction; Spiders; Humorous stories; Horror tales; Mystery and detective stories; Animals -- Insects; Social Themes -- Friendship; Children's stories; Paranormal fiction; Detective and mystery fiction; Fiction; Horror fiction; Humorous fiction; Juvenile works; Mystery fiction